Do Tourism Events Affect Lodging Occupancy Rates? A Case Study Of The Tomohon International Flower Festival, North Sulawesi Province - Kalele, Selvy; Mauren M. Mandagi; Dianne O. Rondonuwu; Bernadain D. Polii; Jemmy Pangemanan; Vesty Like Sambeka; Silvana Mewengkang (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
This paper aims to examine the impact of the Tomohon International Flower Festival on the occupancy rate of lodging. The International event began in 2006 and until now is still being held because it is considered capable of marketing the tourist attractions in the city of Tomohon. Indeed, every time this event is held, it is certain that many tourists and come to visit the location of the activity, because the distance from Manado to Tomohon is > 24km, allowing many guests to come from surrounding cities. It is suspected that guests may stay at hotels in Manado and not stay in Tomohon.The survey was conducted on 100 staff representing different managerial levels; top management, middle management and lower management at 3 different lodgings namely Grand Master Hotel, Emitta Villa and Gardenia Country with the assumption of representing the status of hotel stars, which are in Tomohon City. The analysis used is validity and reliability, simple linear regression and F test. The results showed that there was an effect of the implementation of the flower festival in Tomohon on the occupancy rate of guests at lodging in the city.